Encoding of goal-relevant stimuli is strengthened by emotional arousal in memory - Lee, Tae-Ho; Greening, Steven G.; Mather, Mara (Frontiers in Psychology, 2015)
Emotional information receives preferential processing, which facilitates adaptive strategies for survival. However, the presence of emotional stimuli and the arousal they induce also influence how surrounding non-emotional information is processed in memory (Mather & Sutherland, 2011). For example, seeing a highly emotional scene often leads to forgetting of what was seen right beforehand, but sometimes instead enhances memory for the preceding information. In two studies, we examined how emotional arousal affects short-term memory retention for goal-relevant information that was just seen. In Study 1, participants were asked to remember neutral objects in spatially-cued locations (i.e., goal-relevant objects determined by specific location), while ignoring objects in uncued locations. After each set of objects were shown, arousal was manipulated by playing a previously fear-conditioned tone (i.e., CS+) or a neutral tone that had not been paired with shock (CS-). In Study 1, memory for the goal-relevant neutral objects from arousing trials was enhanced compared to those from the non-arousing trials. This result suggests that emotional arousal helps to increase the impact of top-down priority (i.e., goal-relevancy) on memory encoding. Study 2 supports this conclusion by demonstrating that when the goal was to remember all objects regardless of the spatial cue, emotional arousal induced memory enhancement in a more global manner for all objects. In sum, the two studies show that the ability of arousal to enhance memory for previously encoded items depends on the goal relevance initially assigned to those items